Geoankieta jako forma konsultacji społecznych w planowaniu i zagospodarowaniu przestrzennym - Gulińska, Emilia (The Opole Studies in Administration and Law, 2025)
The present study is devoted to the issue of use of geo-survey as a tool of public participation in the process of creating spatial planning acts. It is founded on the statement that geosurvey as a tool of electronic public participation offers an innovative and effective solution to support the process of spatial planning, in this way enabling inclusion of residents in decision-making activities through interactive acquisition of spatial data. Consequently, it promotes the principles of democratisation, transparency and inclusiveness in public administration. The question arises how the geo-survey implements the idea of electronic public participation and what benefits and limitations arise from the use of the analysed tool in the administrative practice. Accordingly, the goal of this paper is to present the geo-survey as a modern form of public consultation in spatial planning and development. The author aims to discuss the essence, use and importance of the geo-questionnaire as a tool for electronic public participation, enabling collection of spatial data from citizens. She also attempts to assess the effectiveness of this tool in the context of enhancing social dialogue and increasing the transparency and efficiency of planning processes. The considerations in the paper are important for legal sciences, as they contribute to the development of research on the interaction of law with modern technologies, including the instrument of e-administration and e-participation. Application of the geo-questionnaire in planning and spatial development process shows a new dimension of public consultation based on the use of information and communication technologies and spatial information systems. The paper uses a dogmatic-legal method.